Telaah Konseptual Ekonomi Mikro Berbasis Syariah - Billi Jenawi; Devani Tarigan; Reni Ria Armayani Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Islamic economics is a branch of science that discusses economic issues like conventional economic systems. However, what distinguishes it is the application of Islamic values ​​as the main foundation in all economic activities. In the context of Islamic microeconomics, decision-making by each economic actor is carried out by considering the limitations of sharia as the main factor. Here, economic variables only act as necessary conditions, while morality and sharia rules act as sufficient conditions. Islamic economics is present as an alternative solution to global economic problems and as a means to achieve spiritual happiness, because economic activities in this system can also be considered worship.